2016
DOI: 10.2298/pan1601135h
|View full text |Cite
|
Sign up to set email alerts
|

Policy implications and impact of household registration system on Peasants’ Willingness to return rural residential lands: Evidence from household survey in rural China

Abstract: Despite a growing body of literature on China's household registration system and rural land transfer, few studies have examined the impact of the household registration system on peasants' willingness to return rural residential land. This paper aims to fill this gap and uses household survey data to measure the impacts of household registration system on peasants' willingness to return rural residential land. The results show that the household registration system reduced the farmers' enthusiasm to exit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The farmer who was older, was more willing to withdraw from the homestead. This may be because elderly people do less agricultural work and are consequently less dependent on the land and would prefer to receive some compensation or move to a town for their old age [ 16 ]. Our findings are also consistent with those of Wang and Kang [ 71 ], who also found that households with more laborers were more likely to adopt this policy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The farmer who was older, was more willing to withdraw from the homestead. This may be because elderly people do less agricultural work and are consequently less dependent on the land and would prefer to receive some compensation or move to a town for their old age [ 16 ]. Our findings are also consistent with those of Wang and Kang [ 71 ], who also found that households with more laborers were more likely to adopt this policy.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, farmers have their own distinct risk perceptions of specific WRH-targeted events. Overall, these are the four main risks farmers may face because of the WRH, related residence risk, livelihood risk, security risk, and policy risk [ [16] , [17] , [18] ]. Hence, the role of risk perception on farmers’ withdrawal homestead behavior cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong negative decoupling between the rural population and residential land [30]. Meanwhile, the current household registration system reduces the willingness of farmers to withdraw from their homesteads [31], leading to the phenomenon of "people leaving while houses are remaining", which leads to vacant and abandoned homesteads. As a result, problems such as rural hollowing, one household with multiple houses, rural population outflow, and residential land expansion arise.…”
Section: Rural Population and Land Use At Different Urbanization Stagesmentioning
confidence: 99%
“…We examine the effect of reform in rural banking institutions. Second, although existing literature documents the reform-growth nexus in agriculture, farmer income and so on [100][101][102][103][104][105][106][107], they have not identified whether the coordinated interaction and consequent synergism between subsystems inside is the plausible influencing channel. This study estimates the synergism between two subsystems proxied by coupling coordination degree and investigates the effect of the synergism on agricultural growth, farmer income growth, and urban-rural income gap reduction.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%